Espressioni dell'identità Processi e analisi in educazione - FERRARI, MONICA; MORANDI, MATTEO (Scienze della formazione - Open Access, 2019)
The book develops a reflection, shared by the authors, regarding some pedagogical phenomena which individuals and social groups have been involved in, thanks to theoretical and empirical analyses centred on case studies and articulated on two fronts. On the one hand, the topic is that of identity devices connected with specific educational processes, between being and having to be; on the other hand, there is the topic of the body as privileged observation point and region of identity. Different research experiences converge here in a shared path, aimed at an audience that is interested in the educational processes of today and the past, in its relationship with the controversial concept of identity.